Rancang Bangun Sistem Monitoring Suhu & Ph Akuarium Ikan Hias Berbasis IOT (Internet OF Things) Menggunakan Framework Laravel dan Bot Telegram - azmayusuf; Luki Hernando; Zainul Munir; Muhammad Jufri (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2025)
Indonesia possesses significant potential in marine ornamental fish resources with high economic value. One of the main challenges in maintaining koi (Cyprinus carpio), which is popular for its attractive shape and colors, is maintaining a stable aquarium environment. Fluctuations in water temperature and pH can adversely affect the health of the fish, thus an effective monitoring system is necessary. This study employs a waterfall development method to design and build a temperature and pH monitoring system based on the Internet of Things (IoT). The system is developed using the Laravel framework and a Telegram bot to enable real-time monitoring of water conditions and provide automatic notifications to the owner when water conditions fall outside safe limits. Testing results show that the system successfully detects water temperature with an error margin between 1.44% and 2.50%. The results of the pH sensor testing show that the measured pH values range from 6.24 to 7.14. The percentage error in the measurements varies from 2.19% to 14.53% compared to the reference pH value of 7.3. The notification system also performs well, sending alerts when the water pH is below 6.5 or above 7.8, and when the water temperature is below 22°C or above 30°C. The web application effectively displays real-time temperature and pH data and allows control of pH and temperature through commands from the web interface.